EVALUATION OF THE EFFECT OF NPK FERTILIZER AND SPACING ON GROWTH AND YIELD OF GARLIC (ALLIUM SATIVUM) IN BOMET COUNTY - Kioko, Josephat Mwamba David; Kamau, Prof. Peter A.; Mushimiyimana, David (IJRDO- Journal of Educational Research, 2017)
Garlic, of soft neck variety with the silver skin cultivar was evaluated for growth and yields performance under different inorganic NPK (23: 23:0) fertilizer regimes and plant densities. The objectives of the study were to determine bulb yield of garlic grown on four different NPK (23:23:0) fertilizer regimes, to establish the effects planting density on garlic bulb yield and to determine the effects of NPK fertilizer and planting density on garlic yield. From the study it was concluded that spacing and fertilizer application influenced growth and yield of garlic and as such it is important to use appropriate fertilizer and plant density for enhanced garlic productivity among smallholder farmers in Bomet County for improved household incomes from this crop and hence poverty reduction.